EFFECT OF TEMPERATURE ON THE FUNCTIONAL CHARACTERISTICS OF THE CARDIOVASCULAR SYSTEM IN ROWING ATHLETES - Khujabekov Mirzaakhmad Absamatovich (Scholars Digest Publishing, 2023)
This article describes the opinions of foreign scientists about cardiovascular changes in rowing athletes. Temperature dependence of changes in the cardiovascular system of rowers was analyzed.
Keywords: Rowing, cardiovascular system, temperature changes.